2009
DOI: 10.1364/oe.17.013354
|View full text |Cite
|
Sign up to set email alerts
|

Deep tissue multiphoton microscopy using longer wavelength excitation

Abstract: We compare the maximal two-photon fluorescence microscopy (TPM) imaging depth achieved with 775-nm excitation to that achieved with 1280-nm excitation through in vivo and ex vivo TPM of fluorescently-labeled blood vessels in mouse brain. We achieved high contrast imaging of blood vessels at approximately twice the depth with 1280-nm excitation as with 775-nm excitation. An imaging depth of 1 mm can be achieved in in vivo imaging of adult mouse brains at 1280 nm with approximately 1-nJ pulse energy at the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
423
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(444 citation statements)
references
References 32 publications
6
423
0
2
Order By: Relevance
“…MPM allows observation of cellular and subcellular dynamics and functions in deep live tissue within highly complex and heterogeneous environments, providing critical in situ and in vivo information that is difficult to obtain otherwise. Long wavelength excitation can improve the imaging depth (20) but this limits the range of fluorophores that can be employed and still suffers from wavefront distortions (8,17,21). Extending the penetration depth has thus been a major challenge in studying extremely heterogeneous biological samples such as brain and lymphatic tissues.…”
mentioning
confidence: 99%
“…MPM allows observation of cellular and subcellular dynamics and functions in deep live tissue within highly complex and heterogeneous environments, providing critical in situ and in vivo information that is difficult to obtain otherwise. Long wavelength excitation can improve the imaging depth (20) but this limits the range of fluorophores that can be employed and still suffers from wavefront distortions (8,17,21). Extending the penetration depth has thus been a major challenge in studying extremely heterogeneous biological samples such as brain and lymphatic tissues.…”
mentioning
confidence: 99%
“…It is known that SERS has equal or in some cases a greater enhancement of Raman signal when compared to fluorescent markers and that SERS metal substrates produce spectral line widths which are 10-100 times narrower compared to fluorescence [64,318,319]. This means the technique can be used where high selectivity and multiplexing (targeting two analytes at once) is called for since the resolution between peaks will be well defined [320][321][322][323][324][325][326][327][328][329][330][331][332]. In addition, the short Raman scattering lifetime prevents photobleaching and quenching [312,323,324].…”
Section: Sers Immunoassaysmentioning
confidence: 99%
“…For this reason, it is necessary to develop red-shifted tags capable of reaching deep tissue in order to optimize diagnosis and treatment of disease. When Kobat et al compared two excitation wavelengths (775 and 1280 nm) using two photon fluorescence microscopy (TPM) to label and image mouse blood vessels in vivo and ex vivo, the authors found that high contrast images obtained by using 1280 nm excitation had the twice the depth penetration as those obtained at 775 nm [332]. Recently, Bedics et al developed an extreme red-shifted SERS nanotag comprised of chalcogenopyrylium dyes containing phenyl 2-thienyl and 2-selenophenyl substituents (with absorption wavelengths of 1064 nm) on the surface of HGNs (SPR = 720 nm) for use with 1280 nm laser excitation [333].…”
Section: Sers Nanotagsmentioning
confidence: 99%
“…Single-photon confocal laser scanning microscopy does not have these features [12][13][14]. Thus, TPLSM has been widely used and has become an important tool in the field of tumor biology [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%